The Efficacy and Health Economics of Different Treatments for Type 1 Cesarean Scar Pregnancy - Tingting Hong; Zeying Chai; Manman Liu; Lingzhi Zheng; Feng Qi (Frontiers in Pharmacology, 2022)
Objectives: To evaluate the efficacy and health economics of four treatments for type 1 cesarean scar pregnancy (CSP).Methods: From January 2009 to December 2018, 326 patients diagnosed with type 1 CSP were examined, among whom 31 received ultrasound-guided local injection of methotrexate (local injection group), 160 patients received uterine artery embolization combined with suction aspiration (UAE group), 25 patients received ultrasound-guided suction aspiration (aspiration group) and 90 received ultrasound-guided local injection of lauromacrogol combined with suction aspiration (lauromacrogol group). Clinical data and outcomes were analyzed. The decision tree model was used to compare the economics of four treatments.Results: The success rate of the local injection group was 71.0% (22/31), which was significantly different from 98.8% (158/160) of the UAE group and 100.0% (90/90) of the lauromacrogol group. The success rate of the aspiration group was 92.0% (23/25), which was significantly lower than that of the lauromacrogol group. The cost-effectiveness ratio was 1,876.53 yuan for the aspiration group, 2,164.63 yuan for the lauromacrogol group, 4,383.56 yuan for the local injection group, and 7,850.81 yuan for the UAE group. The Incremental cost effectiveness ratio (ICER) of the lauromacrogol group to the aspiration group was 5,477.75 yuan, indicating that if the willing to pay of patients was higher than 5,477.75 yuan, the lauromacrogol group had a cost-effectiveness advantage in treating type 1 CSP, compared to aspiration group. On the contrary, aspiration group has a higher cost-effectiveness advantage. The ICER of the lauromacrogol group to the local injection group or the UAE group were both less than 0, indicating that local injection group and UAE group was not cost-effective in the treatment of type 1 CSP.Conclusion: For type 1 CSP, the ultrasound-guided local injection of lauromacrogol combined with suction aspiration and ultrasound-guided suction aspiration, are effective and economical, and the choice between the two can be based on the patient’s willing to pay.